Strategy for improving pharmaceutical services based on SNARS edition 1 at the "X" hospital pharmacy installation in tomohon city - Priska Juanita Pakingki; Opstaria Saptarini; Tri Wijayanti (Journal of Health Management and Pharmacy Exploration, 2023)
Accreditation is a process of evaluating a hospital by KARS to improve patient safety and evaluate the quality of a hospital. This research was conducted at the "X" Hospital Pharmacy Installation in Tomohon City. To find out the level of conformity of the seven Pharmaceutical Services and Drug Use standards against the 1st Edition of 2018 National Hospital Accreditation Standards and problem solving strategies using a priority scale with the matrix method. The research design is a non-experimental research. analyzed descriptively quantitative and qualitative. The research data were processed in tabular form and repaired with a priority scale of problems using the matrix method. The conformity level of Pharmaceutical Services and Drug Use in the "X" Hospital Pharmacy Installation has not fully met the National Hospital Accreditation Standards. Improvement strategy based on priority scale of problems using the matrix method: Pharmaceutical Services and Drug Use Point 5 Preparation and delivery, Point 4 Prescription and copying, Point 3 Storage, Point 7 Monitoring drug effects, Point 6 Drug Administration, Point 1 Organizing and Point 2 Selection and procurement. Pharmaceutical services in the Pharmacy Installation as a whole are good but there are several points that have not met the standards and must be improved.